2018
DOI: 10.18632/oncotarget.24509
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble CD163 and CXCL5 may be predictive markers for immune-related adverse events in patients with advanced melanoma treated with nivolumab: a pilot study

Abstract: Antibodies against PD-1, such as nivolumab and pembrolizumab, are widely used in the treatment of various cancers including advanced melanoma. The anti-PD-1 Ab significantly prolongs survival in patients with metastatic melanoma, and its administration in combination with local or systemic therapy may also lead to improved outcomes. Although anti-PD-1 Ab-based combined therapy might be effective for the treatment of advanced melanoma, the associated risk of irAEs is an important consideration. Therefore, being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 36 publications
1
75
0
Order By: Relevance
“…To investigate the soluble factors that may correlate with the onset of fever spike, we measured sCD163, CXCL9, CXCL10 and CXCL11 before and after the administration of E + B combined therapy at the time of onset of a fever spike. These soluble factors were reported to correlate with the AE of anti‐PD‐1 antibody 6,10 and with the spike of fever in patients with AOSD 5 . Serum sCD163, CXCL9, CXCL10 and CXCL11 were increased in all three cases in parallel with their fever spike, but not in another three patients who had been treated with immune checkpoint inhibitors previously but did not develop pyrexia by E + B combined therapy (Fig.…”
Section: Case Reportsmentioning
confidence: 86%
“…To investigate the soluble factors that may correlate with the onset of fever spike, we measured sCD163, CXCL9, CXCL10 and CXCL11 before and after the administration of E + B combined therapy at the time of onset of a fever spike. These soluble factors were reported to correlate with the AE of anti‐PD‐1 antibody 6,10 and with the spike of fever in patients with AOSD 5 . Serum sCD163, CXCL9, CXCL10 and CXCL11 were increased in all three cases in parallel with their fever spike, but not in another three patients who had been treated with immune checkpoint inhibitors previously but did not develop pyrexia by E + B combined therapy (Fig.…”
Section: Case Reportsmentioning
confidence: 86%
“…In aggregate, TAM were reported as an optimal target for immunotherapy, 6 and TAMrelated products could even be biomarkers for the efficacy and immune related adverse events in cancer patients. [9][10][11] In this report, we describe two cases in which DT therapy for advanced melanoma failed but were successfully controlled by nivolumab monotherapy. The antitumor effects of nivolumab after DT therapy may be augmented by M1-polarized TAM induced by nivolumab.…”
Section: Discussionmentioning
confidence: 97%
“…reported that reprogramming TAM into inflammatory phenotypes by targeting CD40 and CD115 suppresses melanoma growth in vivo . In aggregate, TAM were reported as an optimal target for immunotherapy, and TAM‐related products could even be biomarkers for the efficacy and immune related adverse events in cancer patients …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the need for predictive markers of treatment efficacy and the development of improved treatment avenues therefore remain as acute as ever [3] . sCD163 and CXCL5 may serve as possible prognostic biomarkers for irAEs in patients with advanced melanoma treated with nivolumab [5] .…”
mentioning
confidence: 99%